A novel Kunitz protein with proposed dual function from Eudiplozoon nipponicum (Monogenea) impairs haemostasis and action of complement in vitro. Issue 5 (April 2019) - Jedličková, Lucie; Dvořák, Jan; Hrachovinová, Ingrid; Ulrychová, Lenka; Kašný, Martin; Mikeš, Libor
Graphical abstract: Highlights: Eudiplozoon nipponicum extract inhibits some peptidases involved in haemostasis/fibrinolysis. En KT1 Kunitz protein inhibits Factor Xa, plasmin and plasma kallikrein. Recombinant En KT1 significantly impairs both haemostasis and complement activation in vitro. Secretory En KT1 may facilitate blood digestion and protect the parasite's gastrodermis. En KT1 is the first parasite Kunitz protein known to affect the host's complement. Abstract: Serine peptidases are involved in many physiological processes including digestion, haemostasis and complement cascade. Parasites regulate activities of host serine peptidases to their own benefit, employing various inhibitors, many of which belong to the Kunitz-type protein family. In this study, we confirmed the presence of potential anticoagulants in protein extracts of the haematophagous monogenean Eudiplozoon nipponicum which parasitizes the common carp. We then focused on a Kunitz protein ( En KT1) discovered in the E . nipponicum transcriptome, which structurally resembles textilinin-1, an antihemorrhagic snake venom factor from Pseudonaja textilis . The protein was recombinantly expressed, purified and biochemically characterised. The recombinant En KT1 did inhibit in vitro activity of Factor Xa of the coagulation cascade, but exhibited a higher activity against plasmin and plasma kallikrein, which participate in fibrinolysis, production of kinins, and complement activation. Anti-coagulation properties of En KT1 based on the inhibition of Factor Xa were confirmed by thromboelastography, but no effect on fibrinolysis was observed. Moreover, we discovered that En KT1 significantly impairs the function of fish complement, possibly by inhibiting plasmin or Factor Xa which can act as a C3 and C5 convertase. We localised Enkt1 transcripts and protein within haematin digestive cells of the parasite by RNA in situ hybridisation and immunohistochemistry, respectively. Based on these results, we suggest that the secretory Kunitz protein of E . nipponicum has a dual function. In particular, it impairs both haemostasis and complement activation in vitro, and thus might facilitate digestion of a host's blood and protect a parasite's gastrodermis from damage by the complement. This study presents, to our knowledge, the first characterisation of a Kunitz protein from monogeneans and the first example of a parasite Kunitz inhibitor that impairs the function of the complement.